Do Geopolitical Risks and Migration Hinder or Stimulate the Renewable Energy Transition? A Wavelet-Based Analysis on the Five Largest Carbon Emitter Countries - Çoban, Serap; Karaman, Gökhan; Çinar, Murat Celal; Ulusay, Nurten (International Journal of Energy Economics and Policy, 2025)
This study analyzes the effects of net migration, geopolitical risk, and economic growth on renewable energy supply in the five largest carbon-emitting countries— the United States, China, India, Japan, and Germany—between 1990 and 2022. Using multi-scale and quantile-based methods, it examines whether these factors hinder or promote the energy transition. Renewable energy supply reflects a country’s clean energy production capacity. Wavelet Quantile Correlation and Wavelet Quantile Regression techniques capture time-frequency interactions and quantile-based differences. Findings show migration boosts renewable energy adoption in migration-receiving countries like the U.S. and Germany but has weaker short-term effects in migration- sending nations like India and China. Geopolitical risks hinder adoption initially, especially in energy-dependent countries, but strong domestic policies in Germany and the U.S. mitigate these risks. Economic growth supports renewable energy in China and Germany but increases fossil fuel reliance in the U.S. and India initially. These results highlight the need for long-term, strategic policies to enhance energy security and sustainability.